Diagnostic and Therapeutic Nuclear Medicine for Neuroendocrine Tumors - Pacak, Karel; Taïeb, David (Contemporary Endocrinology, 2017)
Based on the most novel approaches and cutting-edge clinical and scientific information regarding radionuclide imaging and therapies for neuroendocrine tumors, this clinical guidebook represents a unique collaborative effort between endocrinologists, nuclear physicians, oncologists, surgeons, physicists, radio-pharmacists and geneticists. It begins with the embryology, classification and molecular genetics of gastroenteropancreatic neuroendocrine tumors and carcinoids, chromaffin cell tumors, and MEN1- and MEN2-related tumors. Following a chapter on radiopharmaceuticals in neuroendocrine imaging, it turns to the physics and technology of current and cutting-edge radiology, including SPECT/CT and PET/CT and PET/MR. Discussing of radionuclide imaging covers the tumors mentioned above, as well as pulmonary and thymic neuroendocrine tumors and medullary thyroid carcinoma. A presentation of radionuclide therapies follows, including 131I-MIBG therapy, somatostatin receptor-based therapy, and alpha radionuclide therapy, as well as the role of nanoparticles. Comprehensive and up-to-date, Diagnostic and Therapeutic Nuclear Medicine for Neuroendocrine Tumors will assist and guide physicians who encounter patients with these conditions, either from a diagnostic or therapeutic standpoint, and particularly emphasizes the current and emerging medical devices and imaging and therapeutic options.